Background survey of polyethylene in the Australian Capital Territory – A demonstration of variability in isotopic abundance values and their application to forensic casework. Issue 4 (July 2018) - Jones, Kylie; Koens, Felicity; Simpson, Timothy
Abstract: Plastics including adhesive tapes, cable ties, and packaging are common evidence types encountered in forensic investigations and casework. Traditional examination techniques such as Fourier Transform Infrared (FTIR) spectroscopy lack specificity and are unable to discern differences within the same polymer structures leaving the analyst with a generic identification. High quality manufacturing methods further amplify the limitations in detecting variability between samples. Isotope Ratio Mass Spectrometry (IRMS) has been shown to be a valuable technique in further discriminating plastics. Discrimination is achieved by analysing the relative abundances of stable isotopes within a sample, with differences detected in isotope ratios possibly attributed to the source of raw materials and fractionation during the manufacturing process. A survey of cling wraps and re-sealable zipper storage bags collected in the Australian Capital Territory was undertaken to assess the variability in carbon and hydrogen isotope ratios of different brands and samples. The results of this research are discussed, particularly with respect to within and between brand trends, and a case study is presented as an example of the value of including IRMS in a casework context. Highlights: Research demonstrated isotopic variability of carbon and hydrogen in polyethylene. Ziplock bags and cling wraps collected from the Australian Capital Territory. Research demonstrates value of IRMS for use in forensic comparisons.